2017
DOI: 10.1055/s-0037-1606559
|View full text |Cite
|
Sign up to set email alerts
|

Muscle versus Fasciocutaneous Flap in Lower Limb Reconstruction: Is There a Best Option?

Abstract: Soft tissue defects of the lower extremity that expose underlying bones, joints, and tendons pose challenging problems and generally require free tissue transfer for a successful reconstruction. Historically, muscle flaps were the gold standard choice for lower limb reconstruction. To obviate the unpredictable appearance and high donor-site morbidity of muscle flaps, fasciocutaneous flaps were introduced. Recently, perforator flaps, such as the anterolateral thigh flap, gained a leading role in the reconstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The ease and reliability of reelevating fasciocutaneous free flaps for tendon repairs, delayed nerve repair, bone grafting, or secondary hardware orthopaedic procedures was also reflected in the literature and the articles reviewed in this study. 23,30,38,69 Finally, surgeons should also consider functional outcome, impact, and aesthetic appearance when selecting a flap. There was no significant difference between flap types when assessing physical or social functional outcomes, emotional well-being, general health, or employment rates between either flap types, 26,38 which is consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The ease and reliability of reelevating fasciocutaneous free flaps for tendon repairs, delayed nerve repair, bone grafting, or secondary hardware orthopaedic procedures was also reflected in the literature and the articles reviewed in this study. 23,30,38,69 Finally, surgeons should also consider functional outcome, impact, and aesthetic appearance when selecting a flap. There was no significant difference between flap types when assessing physical or social functional outcomes, emotional well-being, general health, or employment rates between either flap types, 26,38 which is consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…One of the best options for regional reconstruction is the use of muscle flaps, due to its ability to cover injuries, increase local circulation and fight infections [3]. The muscle also provides a good environment for osteogenesis, because of the expression of transforming growth factor-β (TGF-β), interleukine-6 (IL-6) and fibroblast grow factor-2 (TNF-2) [4,5]. Another option is the fasciocutaneous flap, that is less invasive than the muscle flap and has higher blood flow and tissue oxygen tension.…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, primary closure of the donor site is allowed in most of the cases [12]. If all of these flaps were compared, fasciocutaneous and perforator propeller flap provide a relative facility of elevation if a secondary procedure was necessary [5], but muscle flaps are still the best option for covering leg wounds.…”
Section: Discussionmentioning
confidence: 99%
“…2 3 Studies also have indicated there is no difference whatsoever in terms of healing or functional outcome between these two types of flaps in trauma. 4…”
Section: Planning a Flapmentioning
confidence: 99%